Transportation Service Report Information System Using Prototype Method - Cep Adiwiharja; Muhamad Tabrani (Universitas Islam Kuantan Singingi, 2023)
CV. Femarse Inti Mulia, a company engaged in the distribution of products, still processes reporting data, especially payments for transportation services, manually using Microsoft Excel. Problems arising from the old system are errors in the calculation of total wages for transport services for each pen, as well as the occurrence of differences in recording by the warehouse and the finance department. In addition, when using Microsoft Excel formulas, typographical errors can occur, causing calculations to be different than they should be. In light of these problems CV. PT. Femarse Inti Mulia needs an information system for daily transportation service wages reports that is capable of calculating daily transportation service wages, storing this data securely, and managing daily transportation service wages reports easily, quickly, accurately, and in a well-organized manner. The use of information systems for daily wage reports is the right solution to solve existing problems. With the prototype software development method and primary data collection, it makes it easier to design the daily wage report information system.